The Relationship between Knowledge Sharing Capability and Competitiveness of Chartered Public Universities in Kenya - Gachanja, Joseph; Deya, Jared; Muturi, Willy (International Journal of Strategic Management, 2024)
Purpose: The purpose of this study was to establish the relationship between knowledge sharing capability and competitiveness of chartered public universities in Kenya. Universities are knowledge intensive environments, and play a central role in the creation and dissemination of knowledge that they generate. Accordingly, it would be expected that such institutions would adopt proactive approaches to the incubation of knowledge management capability and strategies, and that they would have better insight on how to achieve and optimize the value of their knowledge assets. However, research has shown that this is not the case, and that the approaches adopted by universities are passive and inconsistent. In addition, although there is a strong body of research in the area of knowledge management in commercial environments, and growing interest in knowledge management in public sector organizations, there has been little research on knowledge management capability in universities. Methodology: The study adopted a descriptive design. The population of the research consisted of 31 chartered public universities authorized to operate in Kenya as at December 2020. The study adopted a census methodology while purposeful and convenient sampling was adopted to select respondents amongst the middle level management staff. The study used both secondary and primary data. A self-administered questionnaire was used as the primary data collection instrument. Out of 155 questionnaires that were sent out, 123 were filled and returned. Statistical Package for Social Studies (SPSS) was used for data analysis. The study used regression model to estimate the level of significance which yielded a positive and significant influence of knowledge sharing capability on competitiveness of chartered public universities in Kenya. Findings: The findings pointed out that knowledge sharing capability significantly influenced competitiveness of chartered public universities in Kenya. The public universities should therefore entrench knowledge management practices in their day to day operations in order to remain competitive. Unique Contribution to Theory, Practice and Policy: The study recommended that public universities should embrace knowledge sharing practices in their operations as it enhances competitiveness. One of very important factor in knowledge sharing is that university stakeholders should be accorded with formal, informal and virtual space to interact with each other for knowledge exchange.